(untitled) (Fiep Bulletin - online, 2014)
In physical education, the transformation and the progress of the acquisition of motor function is a process whose effects are relevant for the individual’s formation. It is widely known that mixing the practice of sports and the development of social abilities have been producing good results, which can be observed here in Brazil with the popularization of some sports modalities. This way, sports started gaining space in the social context during last century, but also from private companies and even the creation of a third sector with social sports projects. Mainly because sport is considered a source of health, an element of great educational value, besides involving other values such as: fraternity, cooperation and inclusion. Thus, the educator couldn’t be indifferent to this instrument. For this reason, educational sport as manifestation of the sport-education transformed itself into a preparatory way not only for the sports, being able to generate future athletes but also promoting the citizenship. So, it is possible to ensure to young and to children of underprivileged communities that exists other pedagogical alternatives to their lives. Thus, the purpose of this study was to create a learning swimming method which would be different from other traditional methods. Concepts and divisions of the sport according to theory of Parlebás (2001) were used in order to search a methodological relation of the socio motor function and the psychomotor function to consolidate the creation of a didactic methodology that would enable an effective contact of those children and adolescents with the universe of swimming, objecting the socio motor function ability, as well as promoting the development of the pupil’s personality and emotional capacities; generating interaction between the participants; raising awareness and taste for physical activities since all these elements gather conditions to promote a conscious and effective exercise of the citizenship.